Commodity Price Volatility, Cyclical Fluctuations, and Convergence : What is Ahead for Inflation in Emerging Europe? - Zoli, Edda. (Washington, D.C. : International Monetary Fund, 2009)
This paper assesses the role of international commodity prices, cyclical fluctuations, and convergence in driving inflation in 18 European emerging economies. Country specific VARs and panel estimates indicate that international commodity price shocks have a significant impact on domestic inflation, but the inflation response is asymmetric for positive and negative shocks. Cyclical fluctuations explain a relative small share of inflation variability, and the inflation response is asymmetric during upturns and downturns. Price convergence is estimated to add nearly 3 percentage points to headline inflation, for the average country whose price level is about 50 percent relative to the EU-15 average.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet